Case Report: Polymyxin E-associated reversible leukopenia - Wan, Suxin; Zhu, Jia-Quan; Wang, Lihua (Frontiers in Immunology, 2025)
IntroductionWith the increasing challenge of antibiotic resistance, polymyxin E is considered a last-line treatment option for infections caused by highly resistant bacteria. However, its use may lead to various adverse reactions, such as nephrotoxicity, neurotoxicity, and allergic reactions.Case PresentationThis study describes a case of polymyxin E-associated leukopenia in a 50-year-old female treated for Klebsiella pneumoniae infection. During polymyxin E therapy, the patient developed leukopenia, with white blood cell (WBC) counts declining from 5.65×109/L to 0.91×109/L. The condition resolved progressively after the cessation of polymyxin E. The Naranjo scale yielded a score of 7 for polymyxin E-associated leukopenia, while other medications scored ≤0. The WHO-Uppsala Monitoring Centre (WHO-UMC) causality classification system categorized the relationship as ‘probable.’ConclusionThese findings suggest that polymyxin E likely induces leukopenia, emphasizing the need for rigorous WBC monitoring during treatment and prompt discontinuation when hematologic abnormalities emerge to minimize patient health risks.